THE EFFECT OF PRINCIPAL’S MANAGERIAL ABILITY AND WORK DISCIPLINE ON TEACHERS’ PERFORMANCE IN PUBLIC ELEMENTARY SCHOOLS IN KECAMATAN TAMBAKROMO, KABUPATEN PATI - Wiwik Subekti; Suad Suad; Gunawan Setiadi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to analyze the effect of the Principal's managerial ability on teachers’ performance, the effect of work discipline on teachers’ performance, and the influence of Principal’s managerial ability and work discipline in multiple ways on teachers’ performance. This research was conducted at SD Negeri in Kecamatan Tambakromo, Kabupaten Pati. The type of this study was quantitative research through survey methods to elementary school teachers in Kecamatan Tambakromo, Kabupaten Pati. The samples in this study were 191 respondents, which was selected through incidental techniques. The data collection technique was by giving a questionnaire to the teachers. The data analysis test used validity, reliability, classic assumption tests and multiple linear tests which were processed by using IBM SPSS 24. The results showed the following: (1) Principal’s managerial ability (X1) was proven to have a significant effect on teachers’ performance in SD Negeri in Kecamatan Tambakromo, Kabupaten Pati. The t-test result showed that the sig value. Was equal to 0.000 < 0.05 and tcount 6.520 > ttable 1.9727. (2) Work discipline (X2) was proven to have a significant effect on teachers’ performance in SD Negeri in Kecamatan Tambakromo, Kabupaten Pati. The t-test result showed that the sig value was equal to 0.000 <0.05 and the value of tcount 7.206 > ttable 1.9727. (3) Principal’s managerial ability and work discipline simultaneously proved to have a significant effect on teachers’ performance in SD Negeri in Kecamatan Tambakromo, Kabupaten Pati. The results of the F-test showed that the sig. was equal to 0.000 < 0.05 and the value of fcount 229.714 > ftabel 3.04 and simultaneously influenced the teachers’ performance variable (Y) of 71%.